We are storytelling apes: Experimenting with new scientific narratives in a time of climate and biodiversity collapse - Karen Anderson; Katherine Crichton; Angela Gallego‐Sala (People and Nature)
Abstract Provoked by a lack of appropriate political action on the global climate and biodiversity crisis, we present a perspective advocating and demonstrating a new plurality in scientific communication methods. Science writing, in being objective and dispassionate, actively seeks to mask empathetic connection and hides curiosities that may exist between authors and their subjects. We explain, referencing other work, why scientific writing in academic journal articles is problematic as a singular method of communication that fails to engage non‐specialists. A wealth of existing philosophical work suggests that science translated into stories can deliver a range of valuable outcomes both within science and to wider society. However, such work may not be accessible to busy scientists (i.e. published in non‐science journals, born from different epistemologies, using unfamiliar lexicon) and fails to make simple suggestions about how scientists can implement storytelling themselves. In this perspective, we outline the problems with existing means of engaging people with climate and environmental science, and review storytelling philosophy work, giving examples of how narrative has improved communication, transformed understanding and shifted opinion. We argue for scientific communication models that are beyond objective, both to engage people within science (i.e. across different epistemologies and disciplines) as well as outside of science (i.e. the public and policy makers). We suggest that work that enhances public engagement and trust in science is urgent and of paramount importance, particularly when the policies needed to effect change require huge shifts in behaviour. Crucially, we explain how the augmentation of scientific writing with more narrative forms need not compromise the objectivity of science. Differently from other storytelling in scientific work, we propose three possible ways to diversify environmental science communication and position this piece as a radical intervention into what has become a singularity of otherwise dispassionate scientific writing. Read the free Plain Language Summary for this article on the Journal blog.